RELIGIOUS EXTRACURRICULAR ACTIVITIES ON STRENGTHENING STUDENTS' ISLAMIC IDENTITY - Andi Fitriani Djollong; Erwin; Mohammad Ahmad Bani Amer; Al-Amin (Adisam Publisher, 2024)
Religious extracurricular activities towards strengthening students' Islamic identity refer to a series of activities outside the formal school curriculum designed to deepen the understanding and practice of Islamic teachings among students. The research method used in this study is the literature research method. The results showed that religious extracurricular activities not only strengthen individuals' spiritual understanding and experience, but also promote the application of ethical values in daily life. In addition, these activities support the development of social skills and empathy, and facilitate positive interactions between students from diverse faith backgrounds, encouraging inclusivity and cross-cultural understanding. Finally, this study confirms that religious extracurricular activities play an important role in the formation of communal and personal identities, strengthening individuality while valuing diversity. The implications of the findings suggest that schools should consider including or further developing religious extracurricular programs as an integral part of character education, supporting the formation of ethical, tolerant, and actively contributing young people in a plural society.